IMPLEMENTASI KEBIJAKAN PELAKSANAAN DAN ANALISIS HASIL UJIAN NASIONAL DI KOTA PALU PROVINSI SULAWESI TENGAH - Nur, Muhammad (Katalogis, 2013)
This research was aimed to know how the Implementation Analysis of Authorized Realization and National Examination Result Analysis in Palu City. This research is a qualitative research. The informant of the research was the District Head of Palu city, head master, Head of Committee/Secretary of National Examination, teachers and students’ parents, whereas the sample was drawn purposively which was 7 persons. Data collection method was through observation, interview and documentation. Meanwhile the technique of data analysis used qualitatively. The research used Merilee S. Grendle theory. First, the respect of society toward the orientation and government decision, all respondents accepted the result of national examination conducted but most of them wanted that the determination of national examination given to the school authorization. Second, there is a awareness to accept the authorization, all respondents accepted well the conducting of national examination and there has not been yet another model to replace the national examination. Third, there is a public interest; an authorization if it is on the people side then it has fulfilled the public interest. All respondent told that it has fulfilled. Fourth, there is a law sanction, all respondents told we must follow the rule existed on national examination. Fifth, there is a personal interest on the realization of national examination. Sixth, time problem, all respondents did not have problem with the conducting of national examination when doing the items of national examination because it has examined in every subject.